Hyperbranched Polymers by Light-Induced Self-Condensing Vinyl Polymerization - Aydogan, Cansu; Çiftçi, Mustafa; Yagci, Yusuf (Wiley-V C H Verlag Gmbh, 2018)
Hyperbranched polymers (HBPs), a unique class of dendritic macromolecules, have received continuous interest from macromolecular scientists due to their inherent properties such as high level of functional terminal units, high solubility, and low viscosity. Despite enormous efforts devoted to the synthesis of HBPs by traditional methods such as single and double monomer strategies involving step-growth polymerization and self-condensing vinyl polymerization (SCVP) processes, there have been limited attempts to employ light-induced processes. Photochemical methods, however, exhibit distinct advantages not characteristically disclosed by traditional ones, such as spatial and temporal control, low energy, and site-specific activation. This review, after a brief summary of the conventional methods, presents the unique features and the key functionalities of the inimers for photoinduced SCVP and strategies for preparing HBPs.
Keywords: hyperbranched polymers; light; photopolymerization; polymer synthesis; SCVP